A COL4A4-G394S Variant and Impaired Collagen IV Trimerization in a Patient with Mild Alport Syndrome. Issue 11 (24th November 2022) - Kohler, Jennefer; Omachi, Kohei; Charu, Vivek; Miner, Jeffrey H.; Bhalla, Vivek
Key Points: Missense variants in COL4A genes can cause mild forms of Alport syndrome. Combining pathology and genetics with basic science can successfully determine the pathogenicity of variants of uncertain significance. Low-throughput, mechanistic approaches, applied broadly, may provide a critical next step for precision and personalized medicine. Visual Abstract: Abstract : Background: Missense variants in COL4A genes are often found in patients with an Alport syndrome–like presentation, but their pathogenicity is not always clear. We encountered a woman with microscopic hematuria and proteinuria at 33 years of age with a diagnosis of thin basement membrane disease who was approaching end stage kidney disease at 59 years of age. We hypothesized that this patient's kidney disease was within the spectrum of Alport syndrome. Methods: We used histologic, genetic, and biochemical approaches to investigate the mechanisms of kidney disease. By immunofluorescence, we investigated collagen IV chain composition of the glomerular basement membrane (GBM). We employed targeted sequencing to search for pathogenic variants in COL4A and other relevant genes. We utilized N- and C-terminal split NanoLuciferase assays to determine the effect of a novel COL4A4 variant of uncertain significance (VUS) on collagen IV heterotrimer formation in vitro . We transfected COL4A4 expression constructs with split NanoLuciferase fragment-fused COL4A3 and COL4A5 constructs into human embryonic kidney 293T cells. To assay for α 3 α 4 α 5(IV) heterotrimer formation and secretion, we measured luminescence in cell lysates and culture supernatants from transfected cells. Results: Immunostaining suggested that the collagen α 3 α 4 α 5(IV) network was present throughout the patient's GBMs. DNA sequencing revealed a novel homozygous VUS: COL4A4 c.1180G>A (p. Gly394Ser). In the C-terminal split luciferase-based α 3 α 4 α 5(IV) heterotrimer formation assays, luminescence levels for G394S were comparable to WT, but in the N-terminal tag assays, the extracellular luminescence levels for G394S were decreased by approximately 50% compared with WT. Conclusions: Our cell-based assay provides a platform to test COL4 VUS and shows that G394S impairs assembly of the α 3 α 4 α 5(IV) N-terminus and subsequent trimer secretion. These data suggest that the COL4A4-G394S variant is pathogenic and causes an atypical mild form of autosomal recessive Alport syndrome.